Less is more: Negative income shock increases immediate preference in cross commodity discounting and food demand. (1st October 2018) - Mellis, Alexandra M.; Athamneh, Liqa N.; Stein, Jeffrey S.; Sze, Yan Yan; Epstein, Leonard H.; Bickel, Warren K.
Abstract: Negative income shock, or the rapid reduction in financial stability, has previously been shown to increase impulsive choice for money and demand for fast food. The interplay of these conditions for obesity is called reinforcer pathology. The present work examines the impact of negative income shock on monetary and fast food discounting using a cross-commodity delay discounting task and on purchasing of fast food and an alternative commodity. An obese sample (n = 120) was recruited from Amazon Mechanical Turk and assigned to read one of two narratives: negative income shock (n = 60) or control (n = 60). Participants then completed both within- and cross-commodity discounting tasks of money and food, and purchase tasks for fast food and bottled water. The negative income shock group demonstrated greater impulsive choice across discounting tasks, as well as higher intensity of demand for fast food but not for a non-caloric control commodity (bottled water). These results suggest that negative income shock increases preference for immediate reinforcement regardless of commodity type (money or fast food), but has specific effects increasing demand for particular commodities (fast food but not an alternative). In a reinforcer pathology framework, negative income shock increasing discounting of the future while increasing demand for fast food specifically represents a high-risk state for negative health behavior in obesity.